The Skills of Rewriting Folklore in Class IV Elementary School Students with Video-Assisted - Monica, Ratu Anggia Intan; Sunendar, Dadang (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research aims to describe the skills of fourth-graders at SD Negeri Percobaan in rewriting folk tales. In practice, this research uses a content analysis method with a qualitative approach that has three steps, namely condensing data, presenting data, and drawing conclusions or verification. Data collection techniques in this study used interviews, questionnaires, tests, and documentation to 15 respondents. By paying attention to the findings and discussion, this research has been able to prove the skills of fourth-grade students at SD Negeri Percobaan have skills in rewriting folklore that are not good in terms of content accuracy. The efforts of teachers in improving the skills of rewriting folklore in students are also found through the use of media and learning methods. The theoretical analysis in the discussion provides broad and in-depth information that the skills of students in rewriting folklore in fourth-grade elementary school students are because they have been able and have a good understanding of following the level of development of their age in learning to rewrite folklore so that their skills can improve.